Bridging the Gap Between Fluid Biomarkers for Alzheimer’s Disease, Model Systems, and Patients - Bjorkli, Christiana; Sandvig, Axel; Sandvig, Ioanna (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD) is a debilitating neurodegenerative disease that is characterized by the accumulation of two proteins in fibrillar form: amyloid-β and tau. Despite decades of intensive research, we cannot yet pinpoint the exact cause of the disease or unequivocally determine the exact mechanism(s) underlying its progression. This confounds early diagnosis and treatment of the disease. Cerebrospinal fluid biomarkers, which can reveal ongoing biochemical changes in the brain, can help monitor developing AD pathology prior to clinical diagnosis. Here we review preclinical and clinical investigations of commonly used biomarkers in animals and patients with AD, which can serve as a translational bridge between model systems and clinical populations. The core AD biomarkers have been found to translate well across species, whereas biomarkers of neuroinflammation translate to a lesser extent. Nevertheless, there is no absolute equivalence between biomarkers in human AD patients and those examined in preclinical models in terms of revealing key pathological hallmarks of the disease. In this review, we provide an overview of current but also novel AD biomarkers and how they relate to key constituents of the pathological cascade, highlighting confounding factors and pitfalls in interpretation, and also provide recommendations for standardized procedures during sample collection to enhance the translational validity of preclinical AD models.